Non-saxicolous lecideoid lichens in southern South America - Rodriguez-Flakus, Pamela (Phytotaxa, 2020)
Lecidea Ach. in its broad sense, is one of the largest and most heterogeneous genus of lichenized fungi with a worldwide distribution and with diversity hotspots located in the temperate and polar regions. The genus belongs to a crust-like microlichen group and inhabits many different substrates (e.g., bark, rock, wood, soil, mosses). Lecidea does not form a coherent systematic entity, and previous studies have revealed it as a polyphyletic assemblage with species spread across various families within the Lecanoromycetes. The present study is a modern taxonomic revision of southern South America non-saxicolous lecideoid lichens based on morphological, anatomical and chemical characters. A total of 27 species belonging to ten genera are recognized. The current study reveals a substantial, previously hidden, diversity of lichens in Valdivian temperate and Magellanic subpolar forests; increasing the number of known lecideoid lichens in the studied area. Many new regional records are also reported including six species new to South America (Bryobilimbia hypnorum, Hertelidea botryosa, H. eucalypti, Japewiella tavaresiana, Placynthiella oligotropha, and Ramboldia brunneocarpa). The following species are here described as new to science: Bryobilimbia flakusii Rodr. Flakus sp. nov. (Argentina), B. pallida Rodr. Flakus sp. nov. (Argentina, Chile), Hertelidea printzenii Rodr. Flakus sp. nov. (Argentina), H. stipitata Rodr. Flakus sp. nov. (Argentina, Chile), “Lecidea” vobisii Rodr. Flakus sp. nov. (Argentina), and Ramboldia australis Rodr. Flakus sp. nov. (Argentina, Chile). All species are described and illustrated in detail, and an identification key to the species is provided. In addition, as a result of a revision of available type material, a list of 48 additional species excluded from this study, including brief remarks on their taxonomical affiliations, is provided.